Molecular and Clinical Characterization of Giardia duodenalis Infection in Preschool Children from Lisbon, Portugal. (8th September 2013) - Ferreira, Filipa Santana; Machado Sá da Bandeira, Rita Alexandre dos Santos Soares de Bellegarde; Constantino, Cláudia Alexandra Cecílio de Sampaio Ferreira; Fonseca, Ana Maria Teixeira Duarte Cancela da; Gomes, Joana da Graça Matias; Rodrigues, Rúben Miguel Lopes; Atouguia, Jorge Luís Marques da Silva; Centeno-Lima, Sónia Chavarria Alves Ferreira
Abstract : Giardia duodenalis is the most prevalent intestinal protozoan infection especially in children. In Portugal scarce data are available relative to this infection in preschoolers. The present study was conducted from April to July 2009 in public preschools in Lisbon enrolling 316 children. Stool examination was performed through microscopy. Molecular analysis was conducted in all positive samples for G. duodenalis in order to determine the assemblage and subassemblage of this parasite. Eight of the preschoolers studied children (2.5%, 8/316) were infected with G. duodenalis . Additionally the brother of one of the infected children was also infected. Genotyping analysis targeting ssu-rRNA and β - giardin loci revealed six infections with assemblage A and 3 with assemblage B. Sub-assemblage determination was possible in four of the samples, with three A2 and one A3. The limited number of cases precluded an association of a determined symptom with an assemblage. The data presented here show the relevance of considering G. duodenalis analysis in children with intestinal complaints even in developed countries.